PELAKSANAAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SMP HM LIRBOYO PAPAR PADA MASA PANDEMI COVID-19 - Hasyim, Wakhid (Revorma: Jurnal Pendidikan dan Pemikiran, 2022)
This research discusses the implementation of Islamic Religious Education (PAI) learning during the pandemic. This study wants to show how the planning of Islamic religious to show how the planning of Islamic religious learning during the covid-19 pandemic, how the learning during the covid-19 pandemic, how the learning process during the pandemic at Smp Hidayatul Mubtadiin Lirboyo Papar branch, then how the religious learning process during the covid-19 pandemic, the type of approach used in this study is descriptive qualitativr, the conclusion of this study is the preparation of the learning process of Islamic during the pandemic, the second is limited face to face learning. Because it is in the cottage then there is not much difference during a pandemic or when pandemic learners understand the material to the maximum. And of course it is very strict to implement health protocols, the third is to evaluate Islamic religious education learning during the pandemic, both from teachers, and students.